Reseña descriptiva de la explotación del cuy Cavia porceilus - Escobar L. Gustavo A.; Sanz Oscar R. (Acta Agronómica)
It was revised 241 scientific and empiric references about guinea pig based on which it was formulated a description about such an exploitation this summary is composed of thirteen chapters with the following contents: history, taxonomy, geographical distribution, anatomy, physiology, ethology, nutrition, genetic and improvement, production and handling, soundness, benefic construction and cost production and market. Con base en 241 bibliografías relacionadas con el conocimiento del cuy, se formuló una reseña descriptiva que consta de trece acápites en las siguientes áreas: historia, taxonomía, distribución geográfica, anatomía, fisiología, etología, nutrición, genética y mejoramiento, producción y manejo, sanidad, construcciones y costos de producción y mercadeo.